QoS Improvement in MANET using Self Organized Balanced Optimization (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The provision of quality of service (QoS) for routing in MANET (mobile ad hoc networks) is a major challenge due to the topology, bandwidth sharing and resource scarcity in wireless nodes. Another key aspect of distributing QoS is security, as malicious nodes pose all variety of threats to MANETs. Although a variety of MANET defense measures have been suggested, most solutions are only successful for a particular form of attack or provide security at the risk of sacrificing QoS. A trust-based, secure QoS routing scheme is proposed in this paper by incorporating trust between social and QoS. The key solution of the proposed scheme focuses on minimizing nodes that show different abuses of packet forwarding and finding the way that through the trust mechanism, safe communication is ensured. The performances are compared in in terms of QoS parameters, as channel quality, residual energy, link quality, etc.